A history of the expansion of Christianity ; v. 1 the first five centuries - Latourette, Kenneth Scott 1884-1968 (Exeter, UK Paternoster, 1971)
Includes bibliographical references and index.
First published 1937, Harper and Row, Publishers, New York.
Keywords: Church history -- primitive and early church, ca 30-600.